Age Matching Is Essential for the Study of Cerebrospinal Fluid sTREM2 Levels and Alzheimer’s Disease Risk: A Meta-Analysis - Hu, Shimin; Pan, Na; Liu, Chunyan; Wang, Yuping; Zhang, Tingting (Frontiers in Aging Neuroscience, 2021)
Background: Both genetic and pathological studies link Alzheimer's Disease (AD) to Triggering receptor expressed on myeloid cells 2 (TREM2). A large number of studies have explored the value of cerebrospinal fluid (CSF) Soluble TREM2 (sTREM2) levels as a biomarker for the diagnosis and prediction of AD; however, the findings are inconsistent. Our aims were to review the studies that investigated the association of CSF sTREM2 levels and AD risk, and to provide recommendations for future research. Methods and Results: A systematic literature search was performed using MEDLINE, EMBASE, and Web of Science (all databases). The meta-analysis for the association between CSF sTREM2 levels and AD risk included 15 studies (17 comparisons) with a total of 1153 cases and 1626 controls. The total results showed that higher CSF sTREM2 levels and AD risk were associated (SMD=0.428, 95% CI [0.213, 0.643], I2=81.1%). However, analysis of the subgroup of “age difference ≤ 2 years” indicated that sTREM2 was not associated with AD (SMD=0.090, 95% CI [-0.092, 0.272], I2=27.4%) and got a significantly lower heterogeneity. Combining the results of the "age difference of 5 to 10 years" (SMD=0.497, 95% CI [0.139, 0.855], I2=82.5%) and "age difference >10 years" (SMD=0.747, 95% CI [0.472, 1.023], I2=50.0%) subgroups showed that the difference in CSF sTREM2 between the AD and control groups was positively correlated with the age difference. Meta-regression analysis showed that age difference can explain 33.4% of between-study variance. By conducting further subgroup analyses of the 5 age-matched studies (495 cases and 364 controls) according to measurement method, and whether inclusion criteria containing the requirement for pathological evidence of AD, no changes were observed in the corresponding pooled SMD or in the significance of the results. And the result of “age difference ≤ 2 years” group meta-analysis was robust in the sensitivity analysis. Conclusion: The available high-quality evidence does not yet support an association between CSF sTREM2 levels and AD risk. Age matching between AD patients and cognitively unimpaired controls was a major influence factor in the results.